Prenatal enzymatic diagnosis of lysosomal storage diseases using cultured amniotic cells, uncultured chorionic villus samples, and fetal blood cells: Hacettepe experience. (22nd August 2019) - Unal, Canan; Ozkara, Hatice Asuman; Tanacan, Atakan; Fadiloglu, Erdem; Lay, Incilay; Topçu, Meral; Cakar, Ayse Nur; Beksac, Mehmet Sinan
Abstract : What's already known? Prenatal diagnosis of lysosomal storage diseases is important to avoid high morbidity and mortality. What does this study add? Enzyme analysis may be alone used safely for the prenatal diagnosis of lysosomal storage disases. In populations with a high rate of consanguinity such as ours, prenatal diagnosis of lysosomal storage diseases is also more important due to increased rates of the disease, and enzyme analysis may be chosen for the prenatal diagnosis. Abstract: Aim: To evaluate the results of prenatal enzymatic diagnostic studies for detecting lysosomal storage diseases (LSDs) during 1992 to 2018. Methods: Pregnancies subjected to "prenatal enzymatic diagnosis of LSDs" during 1992 to 2018 were retrospectively evaluated in terms of invasive prenatal tests, type of LSDs, and obstetric outcomes. Results: A total of 142 pregnancies were evaluated for various types of LSDs of which 30, 103, and 9 cases were subjected to amniocentesis, chorionic villus sampling, and fetal blood sampling, respectively. Retrospective analysis of prenatal diagnosis revealed that LSDs affected 33% (47/142) of the fetuses. Sandhoff disease (28%), Tay‐Sachs disease (27%), and metachromatic leukodystrophy (MLD) (20%) were the most frequent LSDs among the evaluated cases with two false negatives, one each for Tay‐Sachs disease and MLD. Conclusion: Enzymatic prenatal diagnoses of certain LSDs may serve as a primary intervention point for families with index cases of infantile or late infantile types of LSDs, since they are associated with poor outcomes, including mortality. In addition, enzyme studies alone may also be feasible for populations with increased risk of molecular heterogeneity, novel mutations, and low‐income settings where genetic analysis is inaccessible.